Children of Divorce amid Allegations of Violence Need Clinical Child Expertise: Adapting Empirically Supported Interventions. Issue 3 (2nd July 2020) - Champion, Kelly M.; Trane, Sarah T.
ABSTRACT: Family structures in the United States have changed dramatically. Almost half of children growing up will spend some portion of their childhood in one of the following arrangements: single parent home, two homes, or living with one parent and a stepparent/intimate partner of their parent. Although child and adolescent mental health-care providers are treating children in families with complicated histories, and evidence supported interventions (ESI) typically include caregivers in child treatment, neither research nor manuals speak to variability in family structure, especially if parents are engaged in frequent court contact on divorce/child-related issues and/or there have been allegations of violence, abuse, or impaired parenting behavior. Children whose parents are frequently in court are vulnerable and also at risk of not having access to ESIs – even when an ESI is strongly indicated. Instead, children may be court ordered to alternative treatments or changes in parenting time after allegations of violence without protective or therapeutic interventions. Mental health clinicians can be informed of these risks, knowledgeable about family violence and prepared to expertly and ethically adapt ESI for this vulnerable population. This paper addresses adaptations in ESI for this population by providing a brief review of the underlying developmental and legal issues at play, recommended adaptations, and using three fictional and representative case studies.